RELIGIOUS RESPONSES TO SUSTAINABLE DEVELOPMENT GOALS: AN ISLAMIC PERSPECTIVE - Foyasal Khan; Mohamed Aslam Haneef (Bank Indonesia, 2022)
This paper investigates the role of religion in Sustainable Development (SD) and offers an Islamic perspective to Sustainable Development Goals (SDGs). Applying a multidimensional approach to development, this paper presents 17 SDGs into the six dimensions —i.e.,Social, Human Capital, Economic, Sustainable Lifestyle, Environmental, and Institutional. From the discusions of the dimensions from Islamic perspective, some key findings are: Islam lays emphasis on human capital development (SDG 3 and 4) which is a key element in accelerating economic Growth (SDG-8). Islam also offers a wide range of social financial tools such as Zakat, waqf that can be used to address SDG 1 (poverty), 2 (hunger), 5 (gender eqaulity), and 10 (reducing inequality). Islamic finance offers a number of tools for long-term financing such as sukuk that can masterfully be used for building sustainable infrastructure (SDG-9) and sustainable cities (SDG-11). This study also reviews some Islamic principles from the Holy Qur'an that can positively promote several SDGs. Wasatiyyah (Moderation) principle can be used for sustainable consumption and production (SDG-12), Khalifah ( God’s vicegerent on Earth) for utilizing Water and sanitation (SDG-6) and energy (SDG-7). Maslahah ( public interest) for dealing with natural resources; Salam (peace), ‘Adl wa al-Ihsan (justice and benevolence) for SDG-16 (peace, justice and strong institutions) and Ta‘āwanū ‘alal-Birri (cooperation one another in goodness) for SDG-17 (partnerships for the goals).